Dynamic Observation of Autophagy and Transcriptome Profiles in a Mouse Model of Bleomycin-Induced Pulmonary Fibrosis - Wang, Yani; Hu, Siqi; Shen, Lisha; Liu, Song; Wan, Linyan; Yang, Shuhui; Hou, Mengjie; Tian, Xinlun; Zhang, Hongbing; Xu, Kai-Feng (Frontiers in Molecular Biosciences, 2021)
Pulmonary fibrosis is a group of progressive, fibrotic, and fatal lung diseases, and the role of autophagy in pulmonary fibrosis is controversial. In the current research, we dynamically observed a bleomycin-induced pulmonary fibrosis mouse model after 3, 7, 14, 21 and 28 days and investigated the expression of autophagy markers. We found that autophagy markers were not significantly changed on the indicated days in the mouse lung tissue. Then, RNA-Seq was used to analyze the gene expression and associated functions and pathways in fibrotic lung tissue on different days post-bleomycin. In addition, short time series expression miner (STEM) analysis was performed to explore the temporal post-bleomycin gene expression. Through STEM, continually up- or downregulated profiles did not demonstrate the critical role of autophagy in the development of fibrosis. Furthermore, gene ontology (GO) annotations showed that continually upregulated profiles were mainly related to fibrosis synthesis, extracellular space, and inflammation while enriched pathways were mainly related to the PI3K-Akt signaling pathway, ECM-receptor interactions and focal adhesion signaling pathway. For continually downregulated profiles, GO annotations mainly involved sarcomere organization, muscle contraction and muscle fiber development. The enriched KEGG signaling pathways were the cAMP signaling pathway, cGMP-PKG signaling pathway, calcium signaling pathway and cardiac muscle contraction. Moreover, we analyzed autophagy-related genes expression in specific cells from publicly available database of 3 human and 1 animal studies of pulmonary fibrosis with single cell sequencing technology. All results consistently demonstrated no critical role of autophagy in the pathogenesis of pulmonary fibrosis. In summary, autophagy may not critically and consistently change during the development of pulmonary fibrosis at different stages post-bleomycin in a mouse model. These continually up- or downregulated profiles, including gene profiles, and the corresponding functions and pathways may provide mechanistic insights into IPF therapy.